Pengaruh Affiliate Marketing dan Online Customer Review Terhadap Keputusan Pembelian Produk Scarlett Whitening (Survey Pada Followers Instagram Scarlett Whitening) - Maulida, Rizka; Siregar, Salim (Peneliti.net, 2023)
The research conducted aims to identify, analyze, and explain the phenomenon between affiliate marketing and online customer reviews on purchasing decisions for Scarlett Whitening products. This research uses a type of quantitative research with descriptive and verification methods. The population in this study is Scarlett Whitening's Instagram followers. The sample to be tested in this study is 400 people with sampling using the Slovin formula. This study used the Non Probability Sampling technique with the Purposive Sampling technique. Data analysis techniques used Scale Range analysis and Path analysis with the help of the Method of Succesive Interval (MSI) and the SPSS software analysis tool version 25. The results of the study show that partially Affiliate Marketing has a positive and significant effect on Purchase Decisions with a percentage of 32.7%. Partially, Online Customer Reviews have a positive and significant effect on Purchase Decisions with a percentage of 3.8%. Simultaneously Affiliate Marketing and Online Customer Reviews have a significant effect on Purchase Decision with a percentage of 36.5% and 63.5% are influenced by other variables not examined.